Quantification and reporting of vitamin D concentrations measured in human milk by LC–MS/MS - Jones, Kerry S.; Meadows, Sarah R.; Koulman, Albert (Frontiers in Nutrition, 2023)
Vitamin D is essential for optimal bone health, and vitamin D deficiency has been associated with an increased adverse risk of pregnancy outcomes, growth and developmental. In early life, and in the absence of endogenous vitamin D production from UVB light, infants are reliant on vitamin D stores established in utero and the vitamin D supply from human milk (HM). However, comprehensive data on vitamin D in HM is lacking. Thus, in this comprehensive review we explore the application of liquid-chromatography tandem mass spectrometry (LC-MS/MS) to the assessment of vitamin D in HM. We discuss the challenges of extracting and measuring multiple vitamin D metabolites from HM including the frequent requirement for a large sample volume, and inappropriate poor sensitivity. Shortcomings in the reporting of experimental procedures and data analysis further hinder advances in the field. Data collated from all studies that have applied LC-MS/MS reveal that, in general, cholecalciferol concentration is greater and more variable than 25-hydroxyvitamin D concentration, and that the vitamin D content of HM is low and less than the currently recommended dietary requirement of infants, although maternal supplementation can increase the vitamin D content of HM. Improvements in analytical methods and their validation and larger, more representative studies are required to better characterise HM milk vitamin D metabolite concentrations and their relationship with maternal status. These are essential to understand relationships with infant health and to inform public health policies around vitamin D fortification and supplementation.